PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS E-COMIC PADA MATERI SISTEM GANGGUAN PENCERNAAN MANUSIA PADA KELAS V DI MI MIFTHAUL ULUM KOTA BATU - Rochima, Amelia; Hanifah, Nur Hidayah (PGMI UNHASY, 2025)
Learning media are tools that assist teachers in delivering lessons, making the material clearer and aligned with learning objectives. Based on observations, Grade V at MI Miftahul Ulum Batu has just begun implementing the Merdeka Curriculum, and the learning media used in the process are still limited. Diagnostic assessment results show that students prefer learning through images or stories.This study aims to develop engaging e-comic-based learning media to enhance students' literacy and reduce boredom during the learning process. The development of the e-comic media is focused on the topic Digestive System Disorders in Humans for Grade V. The research method used is Research and Development (R&D) with the ADDIE development model. The subjects of this study were 34 students from Class V C at MI Miftahul Ulum Batu. Data collection techniques included observation, interviews, questionnaires, as well as pre-tests and post-tests. The questionnaire consisted of validation sheets, while the pre- and post-tests were used to measure student learning outcomes. The product developed in this study is an e-comic as a learning medium.The media expert's validation resulted in a feasibility percentage of 95%, categorized as very feasible. The material expert's validation achieved 94% (very feasible), and validation by a practitioner yielded 91% (very feasible). Student learning outcomes showed an average pre-test score of 48.8 and a post-test score of 88.8. The n-gain score was 0.78, which falls under the high category, indicating a significant improvement in students' learning outcomes Keywords: E-comic, Learning Media, Digestive System Disorders in Humans